The Level Of Community Knowledge About ASF Disease In Wairotang Kelurahan, Alok Timur District, Sikka Regency - Teresita Maxima Ua Lakawolo; Larry R. W. Toha; Novalino H. G. Kallau (Jurnal Veteriner Nusantara, 2022)
African swine fever (ASF) is a double-stranded DNA virus, in the family Asfarviridae and genus Asfivirus that causes infectious disease in pigs with a mortality rate of 100%. Transmission of ASF can occur directly from pigs to pigs and indirectly through the bites of ticks and contaminated equipment. The high mortality rate is caused by a lack of community control over treatment due to a lack of public knowledge about ASF. The purpose of this study was to determine the level of public knowledge about ASF disease in Wairotang Village, Sikka Regency. The research method of this research is descriptive research, the sample in this study is the residents of Wairotang Village obtained by cluster sampling technique and the number used is 96 respondents. The instrument used in this study was a questionnaire. Primary data were processed and analyzed using SPSS and then presented in the form of graphs and tables. The results of the research on the level of community knowledge in Wairotang Village are in the moderate to good category, based on the age group as many as 36 respondents (48%) have sufficient knowledge where the majority are in the productive age, namely the age of 20-55 years, based on the education level of 11 respondents (50 %) where the education held is secondary education, namely elementary school, while based on the type of work as many as 7 respondents (58.3%) have good knowledge about ASF disease, namely working as civil servants and based on indicators of the mode of transmission have sufficient knowledge to less, based on prevention indicators have sufficient knowledge, while based on indicators of ASF causative agents and clinical symptoms have less knowledge.